2022
DOI: 10.3389/fpsyg.2022.902816
|View full text |Cite
|
Sign up to set email alerts
|

Fall Seven Times, Stand Up Eight: Linking Project Management Innovation, Project Governance, and High-Performance Work Practices to Project Success

Abstract: Project managers seem to be puzzled in resolving the global dilemma of project failures across industries. Hence, the present study introduces project management innovation (PMI) as a determinant of project success (PS) and explores whether project governance (PG) and high-performance work practices (HPWPs), strengthen this relationship. To confirm these propositions, study data using adapted scales were collected from project professionals representing software development companies in the emerging IT industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…Umer Zaman and others (2022) were the first to introduce and empirically examine the relationship between project governance, project management innovation, project success, and high-performance work practices. They confirmed that high-performance work practices positively moderate project management innovation and project success (Zaman et al, 2022). Highperformance work practices refer to a set of human resource management practices designed to improve organisational performance by enhancing employee skills, motivation, and involvement (Posthuma et al, 2013).…”
Section: Achieving Organizational Excellence Through High-performance...mentioning
confidence: 84%
“…Umer Zaman and others (2022) were the first to introduce and empirically examine the relationship between project governance, project management innovation, project success, and high-performance work practices. They confirmed that high-performance work practices positively moderate project management innovation and project success (Zaman et al, 2022). Highperformance work practices refer to a set of human resource management practices designed to improve organisational performance by enhancing employee skills, motivation, and involvement (Posthuma et al, 2013).…”
Section: Achieving Organizational Excellence Through High-performance...mentioning
confidence: 84%
“…North (1990) highlighted how government policies shape economic decisions and industry competitiveness. A study by Zaman, Khan, Raza, and Farías (2022) demonstrated how government policies influenced the performance and competitive positioning of industries in emerging markets.…”
Section: Hypothesismentioning
confidence: 99%
“…To implement appropriate project governance, identify postconflict environment impact factors, determine key performance indicators, assess critical success factors, and adopt the best strategy for project performance. Role players must understand political reality, protect cultural property, and engage in capacity building to ensure a stable environment for successful reconstruction (Zaman et al, 2022). A well-defined systematic assessment methodology is essential for project governors and role players to guide the planning process and end results of the development process (Zaman et al, 2022;Haq et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Role players must understand political reality, protect cultural property, and engage in capacity building to ensure a stable environment for successful reconstruction (Zaman et al, 2022). A well-defined systematic assessment methodology is essential for project governors and role players to guide the planning process and end results of the development process (Zaman et al, 2022;Haq et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%